2017
DOI: 10.3389/fcimb.2017.00053
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Induces Reactive Oxygen Species-Mediated Autophagy and Extracellular Trap Formation in Macrophages

Abstract: Aflatoxins are a group of highly toxic mycotoxins with high carcinogenicity that are commonly found in foods. Aflatoxin B1 (AFB1) is the most toxic member of the aflatoxin family. A recent study reported that AFB1 can induce autophagy, but whether AFB1 can induce extracellular traps (ETs) and the relationships among innate immune responses, reactive oxygen species (ROS), and autophagy and the ETs induced by AFB1 remain unknown. Here, we demonstrated that AFB1 induced a complete autophagic process in macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 53 publications
(67 reference statements)
2
34
0
Order By: Relevance
“…Monocyte is the phagocytic mononuclear cells to destroy and recycle tissue debris. The monocytes infiltration in the aflatoxicosis induces external trap formation of macrophages (An et al, 2017).…”
Section: Dmentioning
confidence: 99%
“…Monocyte is the phagocytic mononuclear cells to destroy and recycle tissue debris. The monocytes infiltration in the aflatoxicosis induces external trap formation of macrophages (An et al, 2017).…”
Section: Dmentioning
confidence: 99%
“…According to An et al. (), the augmentation of ROS and NOx levels during intoxication with AFB 1 is associated to cell injury, severe inflammation and tissue damage in several organs, which corroborate the involvement of XO activity and uric acid levels to negative effects during AFB 1 consumption. In summary, the excessive formation of uric acid levels can be considered a mechanism involved in the formation of ROS and NOx, which contribute to oxidative and inflammatory process in fish fed with AFB 1 ‐contaminated diet.…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, FB1‐induced programmed cell death accompanied with autophagy induction in monkey kidney MARC‐145 cells . Aflatoxin B1 (AFB1)‐induced autophagay in macrophages . However, little data are involved in the effects of OTA on autophagy in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…21 Aflatoxin B1 (AFB1)induced autophagay in macrophages. 45 However, little data are involved in the effects of OTA on autophagy in pigs. The present study showed that dietary supplementation of OTA increased autophgayrelated gene Atg5 and LC3 II expression in kidney and spleen, consistent with previous studies about other mycotoxin that AFB1 or DON or HT2 could induce Atg5 and LC3 II expression in macrophages 45 or in porcine intestinal cells 20 or in porcine oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation